Factors for financial restatements: case of public listed companies in Malaysia / Shafinaz Lyana Abu Talib ... [et al.] - Abu Talib, Shafinaz Lyana; Razali, Fatin Adilah; Ahmad, Zaini
This study examines the factors that influence the occurrences of financial restatements among public listed companies (PLCs) in Malaysia. This study focuses on PLCs that were listed on the Main Board of Bursa Malaysia for the financial year of 2005 until 2014 as its sample. On average, restatement companies were found to have paid slightly lower client fees, lower non-audit services (NAS) provision, and have a smaller size of the audit committee compared to non-restatement companies. In addition, it was also found that non-restatement companies choose to hire the Big 4 audit firms. The logistic regression analysis however have revealed that client fees, NAS provision, and the size of audit committee will not influence occurrences of financial restatements. In contrast, the types of auditors have a significant association with incidences of financial restatement. This study reports a negative relationship between the types of auditors and the occurrences of financial restatements. The results of this study could act as a guidance and provide assistance to regulators and policymakers (Bursa Malaysia and Securities Commission) in an attempt at improving existing regulations and guidelines related to financial restatements.